Extended common information model for distribution network production repair platform. (2018) - Ma, Jun; Leng, Hua; Zhu, Jiran; Tang, Haiguo
In order to optimise the process of fault repairs for distribution network, it is necessary to realise standardisation and integration of information for different IT systems in distribution management system (DMS) through common information model (CIM). According to the demand of information integration for fault repairs in distribution network, the paper puts forward CIM extensions for feeder model, assert model, fault handling model etc. in compliance with IEC61968. The proposed CIMs have been used for the information integration between the distribution network production repair platform (DNPRP) and other IT systems. And it is illustrated how to use the integration platform based on CIM to carry out the repair business and improve the quality and efficiency of the distribution network repair. Practical applications of these extension CIMs show that the extension CIMs are reliable, efficient and convenient to exchange information.